1999
DOI: 10.1051/aas:1999362
|View full text |Cite
|
Sign up to set email alerts
|

The Burst Observer and Optical Transient Exploring System (BOOTES)

Abstract: Abstract. The Burst Observer and Optical TransientExploring System (BOOTES) is considered as a part of the preparations for the ESA's satellite INTEGRAL, and is currently being developed in Spain, in collaboration with two Czech institutions. It makes use of two sets of wide-field cameras 240 kms apart, and two robotic 0.3-m telescopes. The first observing station (BOOTES-1) is located in Huelva (Spain) and the first light was obtained in July 1998. During the test phase, it has provided rapid follow-up observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 1 publication
0
42
0
1
Order By: Relevance
“…The TAROT observatory demonstrated that this is possible, provided that the alert is sent quickly by the instrument. The increase in the HETE performances, the recent successful launch of the Curie-INTEGRAL satellite, as well as the perspective of the SWIFT GRB dedicated satellite gives hope that rapid observations of GRB optical counterparts will be soon possible, as it was the case with BATSE (Akerlof et al 1999;Boër et al 2001;Castro-Tirado et al 1999;Park et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The TAROT observatory demonstrated that this is possible, provided that the alert is sent quickly by the instrument. The increase in the HETE performances, the recent successful launch of the Curie-INTEGRAL satellite, as well as the perspective of the SWIFT GRB dedicated satellite gives hope that rapid observations of GRB optical counterparts will be soon possible, as it was the case with BATSE (Akerlof et al 1999;Boër et al 2001;Castro-Tirado et al 1999;Park et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there are no other systems similar to the network of optical, broadband MASTER telescopes in Russia, and the main characteristics of the MASTER network (field of view, limiting magnitude, bandwidth, synchronous photometry, polarization-sensitive photometry, pointing speed) exceed other such modern systems worldwide (ROTSE-III [3], TAROT [4], PROMPT [5], BOOTES [6]). …”
Section: Introductionmentioning
confidence: 99%
“…Typically the aspect ratio of such mirrors is around 1/8 [22]. Therefore, taking the uniformly increasing the disk (d ~r, M ~r 3 ), we find that I ~r 5 . The damping amplitude is proportional to exp[-t/t 0 ], where t 0 is proportional to I, thus the time constant (i.e.…”
Section: Discussionmentioning
confidence: 96%
“…The damping amplitude is proportional to exp[-t/t 0 ], where t 0 is proportional to I, thus the time constant (i.e. settling time) is also proportional to r 5 . Now one can reduce the mass (M) and thickness (d) substantially, otherwise it would be extremely expensive to use such mirrors in space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation